(untitled) (Patan Pragya, 2019)
Menstruation is not just a physiological phenomenon but it is also psychological, social as well as behavioral transition for an adolescent girl from girlhood to womanhood. Menstrual hygiene is most important, still neglected area of concern. A cross sectional study was undertaken in a four community schools of rural area of Tanahun district. A pre-designed, self-administered close ended (structured) questionnaire was prepared for collection of data. There were 196 participants for the study. It was marked that 69 percent participants were aware about menstruation before their menarche and the most important sources of information were mothers in 61 percent, 59 percent participants used only sanitary napkin during menstruation, 50 percent changed absorbent 1 to 2 times a day. Although knowledge was better than practice, however, both were not satisfactory level. So, the girls should be educated more about the process and significance of menstruation.